A new high speed charge and high efficiency Li-Ion battery charger interface using pulse control technique - Mustapha El Alaoui; Karim El Khadiri; Rachid El Alami; Ahmed Tahiri; Ahmed Lakhssassi; Hassan Qjidaa (International Journal of Electrical and Computer Engineering (IJECE), 2022)
A new Li-Ion battery charger interface (BCI) using pulse control (PC) technique is designed and analyzed in this paper. Thanks to the use of PC technique, the main standards of the Li-Ion battery charger, i.e. fast charge, small surface area and high efficiency, are achieved. The proposed charger achieves full charge in forty-one minutes passing by the constant current (CC) charging mode which also included the start-up and the constant voltage mode (CV) charging mode. It designed, simulated and layouted which occupies a small size area 0.1 mm2 by using Taiwan Semiconductor Manufacturing Company 180 nm complementary metal oxide semi-conductor technology (TSMC 180 nm CMOS) technology in Cadence Virtuoso software. The battery voltage VBAT varies between 2.9 V to 4.35 V and the maximum battery current IBAT is 2.1 A in CC charging mode, according to a maximum input voltage VIN equal 5 V. The maximum charging efficiency reaches 98%.